DEVELOPMENT OF A STUDENT DECISION-MAKING MODEL IN COLLEGE SELECTION: THE ROLE OF STUDENT INTEREST AS A MEDIATOR OF WORD OF MOUTH (WOM), PRICE AND PROMOTION AT STIE MBI DEPOK - Aan Yulianto; Zaharuddin Zaharuddin; Sitta Kusuma (Jurnal Education and Development, 2026)
This study aims to determine the influence of word of mouth (WOM), price, and promotion on students' decisions in choosing a college through student interest at STIE MBI Depok. The method used in this study is a descriptive verification method with a quantitative approach. The sample in this study was 125 students from the 2024/2025 academic year. The data analysis technique used the SEM-PLS method with the help of the computer application program Smart-PLS Version 3.0. The research results show that word of mouth (WOM) has a significant influence on students' interest and decisions in choosing a university. Price does not directly influence students' decisions in choosing a university, but indirectly, price influences students' decisions in choosing a university through student interest. Promotion does not directly influence students' decisions in choosing a university, but indirectly, promotion influences students' decisions in choosing a university through student interest. Thus, student interest plays a crucial mediating role in bridging the influence of word of mouth (WOM), price, and promotion on prospective students' final decisions in choosing a university. This strategic role of interest indicates that increasing word of mouth (WOM), perceptions of competitive prices, and effective promotional strategies need to be directed at generating interest first to generate positive actual decisions regarding university selection.